1991
DOI: 10.1172/jci115473
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil migration across a cultured intestinal epithelium. Dependence on a CD11b/CD18-mediated event and enhanced efficiency in physiological direction.

Abstract: Clin. Invest. 1991. 88:1605-1612

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
375
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(399 citation statements)
references
References 36 publications
(36 reference statements)
17
375
1
1
Order By: Relevance
“…PMN transepithelial migration can be viewed as a multi-step response that can be initiated by both host and pathogen derived stimuli such as IL-8 and N-formylated peptides respectively (Prossnitz & Ye 1997, Tavares-Murta et al 2002, Ramos et al 2003) From our studies and those of others (Parkos et al 1991, Tosi et al 1992, Agace et al 1995, it is clear that the β2 integrin CD11b/CD18 is central in regulating early adhesive events in the transepithelial migration response. PMN adhesion to epithelial monolayers can be blocked using monoclonal antibodies to CD11b, and furthermore, using specific antibodies in mapping studies, it was demonstrated that a domain consisting of 200 amino acids (I domain) is a major binding region for CD11b/CD18 ligands, including those on intestinal epithelial cells (Parkos et al 1991, Balsam et al 1998. While investigators have actively sought to identify epithelial ligands for CD11b/CD18 over the past decade, only recently have clues emerged uncovering the nature of these cellular ligands.…”
Section: The Molecular Basis Of Pmn Transepithelial Migrationmentioning
confidence: 59%
“…PMN transepithelial migration can be viewed as a multi-step response that can be initiated by both host and pathogen derived stimuli such as IL-8 and N-formylated peptides respectively (Prossnitz & Ye 1997, Tavares-Murta et al 2002, Ramos et al 2003) From our studies and those of others (Parkos et al 1991, Tosi et al 1992, Agace et al 1995, it is clear that the β2 integrin CD11b/CD18 is central in regulating early adhesive events in the transepithelial migration response. PMN adhesion to epithelial monolayers can be blocked using monoclonal antibodies to CD11b, and furthermore, using specific antibodies in mapping studies, it was demonstrated that a domain consisting of 200 amino acids (I domain) is a major binding region for CD11b/CD18 ligands, including those on intestinal epithelial cells (Parkos et al 1991, Balsam et al 1998. While investigators have actively sought to identify epithelial ligands for CD11b/CD18 over the past decade, only recently have clues emerged uncovering the nature of these cellular ligands.…”
Section: The Molecular Basis Of Pmn Transepithelial Migrationmentioning
confidence: 59%
“…Normal human polymorphonuclear leukocytes (PMNs) were isolated, as described previously by Edens et al (42). PMN transmigration experiments were performed as previously described in detail (68). Briefly, inserts were washed 2 times with PBS, placed into new wells containing HBSS (Sigma-Aldrich), and allowed to equilibrate for 15 minutes.…”
Section: Figurementioning
confidence: 99%
“…The buffy coat was obtained via a spin at 400´g at room temperature. Plasma and mononuclear cells were removed by aspiration, and the majority of erythrocytes were removed by a 2% gelatin sedimentation technique described previously (Henson and Oades, 1975;Parkos et al, 1991). Residual erythrocytes were then removed by gentle lysis in cold NH 4 Cl lysis buffer.…”
Section: Neutrophil (Pmn) Transepithelial Migration Assaymentioning
confidence: 99%
“…7. Before the addition of PMNs in this assay system, con¯uent, inverted T84 polarized monolayers (3.5´10 5 cells/well) (Parkos et al, 1991;Madara et al, 1992) were rinsed extensively in HBSS( ) to remove residual serum components. Cultures of S.¯exneri strains were prepared by washing the bacteria twice in HBSS( ) and resuspending in 300 ml buffer/10 ml culture (®nal concentration <1.5´10 9 bacteria ml À1 ).…”
Section: Neutrophil (Pmn) Transepithelial Migration Assaymentioning
confidence: 99%
See 1 more Smart Citation